Improving Student Discipline Through the Application of the Digital Multimedia-Based Token Economy Method in Learning Pancasila Education in Elementary School - Rabia S. Manto (Program Studi PGSD Universitas Madako Tolitoli, 2026)
Departing from the low discipline of grade V students at SDN 4 Bokat which has an impact on the lack of optimal learning process of Pancasila Education is the central problem of this research. To overcome these problems, a digital multimedia-based token economy method was applied through Class Action Research in two cycles that included the planning, implementation, observation, and reflection stages involving 20 students. The results of the study showed a significant increase in student discipline, marked by an average pre-action score of 71.76 with 35% completeness, increasing in the first cycle to 85%, and reaching an average of 100 with 100% completeness in the second cycle. This improvement shows that the integration of the Token Economy with digital multimedia is able to create more interesting, structured, and motivating learning for students. Conceptually, these findings confirm the effectiveness of positive reinforcement in shaping disciplinary behavior. The implications of this study show that teachers can adopt technology-based token economy strategies as an innovative alternative in classroom management, while encouraging the development of learning practices that are more interactive, adaptive, and oriented towards student character formation in elementary schools.